Lead exposure dose-dependently affects oxidative stress, AsA-GSH, photosynthesis, and mineral content in pakchoi (Brassica chinensis L.) - Tan, Zhanming; Wu, Cuiyun; Xuan, Zhengying; Cheng, Yunxia; Xiong, Renci; Su, Zhihang; Wang, Desheng (Frontiers in Plant Science, 2022)
Lead (Pb) is a heavy metal pollutant and negatively affects agriculture and ecosystems. Pb can cause oxidative stress and abnormal plant growth. The ascorbic acid-glutathione (AsA-GSH) cycle mainly exists in chloroplasts and resists oxidative stress, scavenges reactive oxygen radicals, and maintains normal photosynthesis. However, the dosage related effects of Pb on pakchoi photosynthesis, via oxidative stress and the AsA-GSH system, remains unclear. In this study, various Pb dosage stress models were tested (low: 300 mg/kg; medium: 600 mg/kg; high: 900 mg/kg). Pb stress induced a dose-dependent increase in Pb content in pakchoi leaves (P < 0.05). Principal component analysis showed that Se, B, and Pb were significantly and negatively correlated. Pb stress also increased MDA content and decreased antioxidant enzymes SOD, GSH-Px, and T-AOC activities (P < 0.05). We also found that Vc content, as well as the GSH/GSSG ratio, decreased. Additionally, Pb stress destroyed chloroplast structure, decreased photosynthesis indicators Pn, Tr, Gs, Ci and VPD, and attenuated Fv/Fm and Fv/Fo (P < 0.05). In the high-dose group, the contents of chlorophyll a, chlorophyll b, and carotenoids decreased significantly, while the expression of chloroplast development genes (GLK, GLN2) decreased (P < 0.05). Our data suggest that Pb stress leads to dosage-dependent, aberrant photosynthesis by inhibiting the AsA-GSH system in pakchoi. This study expands the Pb toxicology research field and provides indications for screening antagonists.